2016
DOI: 10.1038/srep35566
|View full text |Cite
|
Sign up to set email alerts
|

Diamond photonics platform enabled by femtosecond laser writing

Abstract: Diamond is a promising platform for sensing and quantum processing owing to the remarkable properties of the nitrogen-vacancy (NV) impurity. The electrons of the NV center, largely localized at the vacancy site, combine to form a spin triplet, which can be polarized with 532 nm laser light, even at room temperature. The NV’s states are isolated from environmental perturbations making their spin coherence comparable to trapped ions. An important breakthrough would be in connecting, using waveguides, multiple di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 53 publications
8
97
0
2
Order By: Relevance
“…It is shown that the presence of the waveguide does not adversely affect the properties of the NV defect making this a promising platform for quantum technologies 40 .…”
Section: Arxiv:160600170v2 [Physicsoptics] 28 Jul 2016mentioning
confidence: 99%
“…It is shown that the presence of the waveguide does not adversely affect the properties of the NV defect making this a promising platform for quantum technologies 40 .…”
Section: Arxiv:160600170v2 [Physicsoptics] 28 Jul 2016mentioning
confidence: 99%
“…NbN-based SNSPDs have been fabricated on polycrystalline diamond surface grown via chemical vapor deposition (CVD) on a silica-onsilicon wafer [109,111] (see Figure 4c). Electro-optomechanical The recently demonstrated femtosecond laser based bulk diamond writing technique [112] may hold potential for flexible waveguide definition. Contrary to III-V QDs, the most promising color centers in diamond emit at wavelengths below 1 μm, which hurdles the prospects of long distance communication.…”
Section: Bulk Diamond and Diamond-on-insulatormentioning
confidence: 99%
“…27 Similarly, when writing optical waveguides using the stress field generated by modifications in Regime (ii), the propagation losses are significantly lower than those expected from a complete conversion of the irradiated zones to graphite. 23 These observations indicate that the wires' internal structure is more complex than suggested by optical imaging. As illustration, a recent scanning electron microscopy (SEM) study of subsurface DLW structures exposed by mechanical polishing revealed a main fracture containing graphenic carbon and smaller conductive nanocracks propagating from it.…”
mentioning
confidence: 49%
“…However, previous Raman studies revealed only the partial formation of sp 2 bonded graphite within the laser irradiated zones. 14,19,23,24 When using such modifications to create wires, the resultant resistivity varies from 0.02 to 2 X cm, [18][19][20]25,26 with values at least an order of magnitude higher than that for polycrystalline graphite. 27 Similarly, when writing optical waveguides using the stress field generated by modifications in Regime (ii), the propagation losses are significantly lower than those expected from a complete conversion of the irradiated zones to graphite.…”
mentioning
confidence: 99%
See 1 more Smart Citation